5v=-2v-3v

Simple and best practice solution for 5v=-2v-3v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5v=-2v-3v equation:


Simplifying
5v = -2v + -3v

Combine like terms: -2v + -3v = -5v
5v = -5v

Solving
5v = -5v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '5v' to each side of the equation.
5v + 5v = -5v + 5v

Combine like terms: 5v + 5v = 10v
10v = -5v + 5v

Combine like terms: -5v + 5v = 0
10v = 0

Divide each side by '10'.
v = 0.0

Simplifying
v = 0.0

See similar equations:

| -4y-12=3y+16 | | 9(x+8)=8(x-8)+x | | 5(1+4x)=2(3+10x) | | 2(n-4)=4(5-2n) | | 11x-21=8x | | w-4(w+2)=7-2w | | n^2-12+4n+11=76 | | 4a^2b^2-5ab= | | 13+7x=9+15x | | X*x+x+3=196+x-4 | | 50x^2=32 | | 4(3z-5)=8 | | 4(2/5)+k=-32/11 | | -1.32=3(1.5x-0.5) | | x^2-6y+y^2-7=0 | | 4.5x^2-9x+3.5=0 | | 8y-2=-6y+50 | | -10=2+2.4w | | 5.8-1.4=16 | | 9(g+2)-4=7g+3(3g+8) | | 7(st)=(7s)t | | 5w+a=4.8+8w | | -(3b-15)=6(2hb+5) | | -4m-23=5 | | 2y=-5x+12 | | 5w+9=4.8+8w | | 25+5x=-80-2x | | -4.9t^2+355t+87=0 | | 22(2y+1)= | | 2x+2(2x+8)=772 | | 20-2z=26 | | 3z-4z=2 |

Equations solver categories